Clinical profile and laboratory characteristics of dengue fever in children: analysis of 2019 outbreak from Bengaluru, Karnataka, India - Shankar, Poornima; Mahamud, Shajna (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue, an endemic disease in most subtropical and tropical regions of the world is causing severe epidemics in India. An alarming rise of dengue has also been seen in India during the recent years. Majority of dengue viral infections are self-limiting, but complications may cause high morbidity and mortality. Present study was undertaken with an objective of describing various clinical presentations as noted in our cohort of dengue patients and to evaluate the outcome of dengue fever. Methods: This retrospective study included all confirmed dengue cases below 18 years age admitted to Paediatric department of KIMS, Bengaluru over a period of 1 year in 2019. Medical records were reviewed and analysed. Those diagnosed to be positive for dengue serology (NS1 or IgM) were included in our study. Dengue was classified according to the WHO guidelines into 2 groups, Dengue fever (without/with warning signs) and Severe Dengue. Clinical features, haematological, biochemical, radiological parameters, management and the outcome were assessed. Results: Out of 441 patients enrolled, 79% had non-severe dengue and 21% severe dengue. The commonest age of presentation was above 10 years with mean age of 8.68±5.25 years. Male to female ratio was 1.7:1. 60% presented within 4 to 7 days of illness (mean 4.26±1.72 days). Majority presented with fever (88%). 47% had vomiting and 31% abdominal pain. Bleeding manifestations were seen in 18%. Dengue serology was positive for NS1Ag (58%), IgM (21%), mixed (21%). Thrombocytopenia and leukopenia seen in 82% and 39.45% respectively. The association between dengue serology and platelet count was statistically significant (p value 0.001). 46% had raised SGPT. 31% had evidence of plasma leakage. The case fatality rate was 0.2%. Conclusions: High grade fever, vomiting, abdominal pain and bleeding manifestations with normal or low platelet count were the presenting features. Early diagnosis, monitoring and prompt supportive management can reduce mortality.